Rethinking gender in disability issues - Beigi, A.B.; Cheng, K.K.Y. (Kluwer (now part of Springer), 2010)
In many studies related to gender and disabilities, the focal point has mostly centered on women and their rights related to disability issues. However, by this approach many men with disabilities might be placed at a disadvantage. The inclusion of men in gender and disability issues can contribute to mainstreaming sexuality in this line of research.